Enhancement of High-Order Harmonic Generation due to the Large Gradient of the Electric Field Amplitude - Meiyan Qin; Yi Zeng; Xin Zeng; Qing Liao (Applied Sciences, 2019)
The influence of the waveform of circularly polarized laser field on high-order harmonic (HH) generation from atoms is investigated by solving the time-dependent Schrödinger equation (TDSE) and by classical trajectory analysis, without assuming an initial transverse velocity. Both the HH simulation and the classical trajectory calculation demonstrate that the positive temporal gradient of the electric field amplitude is a key factor that makes the electron return to the parent ion possible. Moreover, the larger the temporal gradient of the field amplitude is, the more the electron trajectories will revisit the parent ion. Correspondingly, the enhancement of HH is observed. This is confirmed by the pulse-duration dependence of the harmonic yield driven by a circularly polarized laser field.